Impact of trade openness on economic growth, youth unemployment and poverty in Sub-Saharan African countries - Peter, Adamu (2017)
This study investigates the impact of trade openness on economic growth, youth unemployment and poverty in Sub-Saharan African (SSA) countries. Trade openness is largely viewed as a channel to boost economic growth for countries. However, the benefits embedded in free trade have not being visible for the SSA region because the economic growth is still low. Other regions where the environment for doing business are attractive to investors and operate relatively better institutions have benefitted immensely from trade openness but SSA have shown dismal performance over the years. Mixed findings have been largely reported in empirical literature for trade openness economic growth nexus but in recent times, the proxy for trade openness and methods applied in the past have been questioned. This suggests the application of new proxies and methods to investigate the trade openness-growth nexus for 40 SSA countries for the period 2000-2014. Similarly, the soaring youth unemployment problem in SSA was investigated on the basis of free trade in the region since international trade theory supports an employment gain for trading partners. The high rate of youth unemployment is worrisome in the face of poor institutions and difficult business environment in SSA. However, recent literature have suggested that goods institutions and business environment are channels through which trade openness can reduce unemployment and this situation was examined for 41 countries in SSA for the period 2000-2014. Despite the participation of SSA in world trade since the inception of WTO, poverty level have reduced only minimally. If trade openness is a poverty reducing arrangement, the poverty level in SSA should have fallen over the years but literature suggests that trade policies are to be complemented with sound policies if they must thrive. Consensuses as to whether trade openness reduces poverty have not been reached and this was investigated for 44 countries in SSA for the period 2000-2014. The first objective of the study is to examine the impact of trade openness on economic growth by considering the role of institutional quality and business environment on the nexus using the threshold regression analysis. The threshold result revealed that trade openness is significant and positive in promoting economic growth up to a certain extent but this positive effect disappears beyond the threshold level because the p-value was found to be insignificant. This suggests that improving trade openness at an early stage of development is necessary to trigger economic growth up to a certain level of trade openness. In the case of institutional quality and business environment, threshold effects are insignificant. However, both domestic and foreign investments as well as human capital are veritable means to develop the SSA region as shown in the results. Secondly, the issue of youth unemployment in SSA was investigated from the perspective of trade openness using the generalized method of moment (GMM) approach. The results revealed that good institutions are essential to reduce youth unemployment when free trade is practiced but poor institutions trigger an increase in youth unemployment in an era of free trade. More essential is a good environment for doing business for countries where trade openness polices are promoted but unconducive business environment can aggravate the problem of youth unemployment in the SSA region. Lastly, the third objective of the study examine the effects of trade openness on poverty in SSA by considering the role of institutional quality and business environment utilizing generalized method of moments (GMM) estimation technique. Using an estimated index known as policy induced openness as a proxy for trade openness against the popular trade shares proxies, the result shows that trade openness aggravates the problem of poverty in SSA when considered directly. However, the indirect effect shows that business environment and institutional quality reduces poverty. Policies to encourage economic growth are necessary since growth reduces poverty and enrolments into schools are vital instruments to alleviate poverty in the SSA region as reported in this finding. Since the effects of trade openness on growth kicks in before trade openness reach a certain threshold, policy makers should improve mechanisms that promote openness such as reducing tariffs, abolishing quotas, and non-tariff barriers to explore the benefits of trade reforms in promoting economic growth in the region.